Risk of First Onset Stroke in SSRI-Exposed Adult Subjects: Survival Analysis and Examination of Age and Time Effects - Chan, Chin-Hong; Huang, Hsiang-Hsiung; Lin, Ching-Heng; Kuan, Yi-Chun; Loh, El-Wui; Lan, Tsuo-Hung (The journal of clinical psychiatry, 2017)
Exposure to selective serotonin reuptake inhibitors (SSRIs) has been shown to increase the risk of stroke. In this study, we investigated age and time effects on the risk of first onset stroke in SSRI-exposed (SSRIEXP) adult subjects. We analyzed an 8-year cohort from the National Health Insurance Research Database, Taiwan. Patients were defined as SSRIEXP subjects if they received SSRI prescriptions for at least 2 consecutive months during January 1, 2001, to December 31, 2007. Otherwise, they were categorized as SSRI-nonexposed (SSRINONE) subjects. Stroke diagnosis was made according to ICD-9 codes 430-432 (hemorrhagic stroke) and 433-437 (ischemic stroke). Kaplan-Meier survival analysis showed a greater probability of first onset stroke in SSRIEXP than SSRINONE subjects (P < .001). The higher incidence rates in SSRIEXP subjects persisted to the 3 year time point. Ischemic/hemorrhagic stroke cumulative incidence ratios were also higher during the first 3 years in SSRIEXP subjects. Analysis of adjusted hazard ratios indicated that younger SSRIEXP subjects were more likely to experience stroke, with a slight increase of risk in subjects older than 65 years. Stratified analysis of ischemic stroke and hemorrhagic stroke resulted in a similar hazard ratio trend. Use of SSRIs independently increases the risk of stroke across age strata. The risk is higher in younger adult subjects, and the stroke is more likely to be ischemic than hemorrhagic. The underlying mechanisms of stroke may be related to cerebral microbleeding or an overcorrection of hemostasis function.